A common pathway for O‐linked protein‐glycosylation and synthesis of capsule in Acinetobacter baumannii. Issue 5 (12th July 2013) - Lees‐Miller, Robert G.; Iwashkiw, Jeremy A.; Scott, Nichollas E.; Seper, Andrea; Vinogradov, Evgeny; Schild, Stefan; Feldman, Mario F.
Summary: Multi‐drug resistant strains of Acinetobacter baumannii are increasingly being isolated in hospitals worldwide. Among the virulence factors identified in this bacterium there is a general O ‐glycosylation system that appears to be important for biofilm formation and virulence, and the capsular polysaccharide, which is essential for resistance to complement killing. In this work, we identified a locus that is responsible for the synthesis of the O ‐pentasaccharide found on the glycoproteins. Besides the enzymes required for the assembly of the glycan, additional proteins typically involved in polymerization and transport of capsule were identified within or adjacently to the locus. Mutagenesis of PglC, the initiating glycosyltransferase prevented the synthesis of both glycoproteins and capsule, resulting in abnormal biofilm structures and attenuated virulence in mice. These results, together with the structural analysis of A. baumannii 17978 capsular polysaccharide via NMR, demonstrated that the pentasaccharides that decorate the glycoproteins are also the building blocks for capsule biosynthesis. Two linked subunits, but not longer glycan chains, were detected on proteins via MS. The discovery of a bifurcated pathway for O ‐glycosylation and capsule synthesis not only provides insight into the biology of A. baumannii but also identifies potential novel candidates for intervention against this emerging pathogen.